Case report: The use of metagenomic next-generation sequencing to diagnose Lemierre’s syndrome caused by lost root canal fillings in a 33-year-old patient with metabolic syndrome - Zhou, Yimeng; Zhai, Yongzhen; Wang, Yan; Zhang, Dan; Feng, Guohe (Frontiers in Medicine, 2024)
Background: Lemierre's syndrome is a rare and serious complication of pharyngitis with an estimated annual incidence of 1 in 100,000 peoples worldwide. It is characterized by septic thrombophlebitis of the internal jugular vein with metastatic infection, usually following oropharyngeal infection. Rare cases are reported to be caused by odontogenic infection.Case Report: A 33-year-old male came to our hospital because of fever and sore throat for 16 days. Symptoms also included pain in his left neck and shoulder. Metabolic syndrome was diagnosed according to waist circumference, diabetes, and hyperlipidemia. Fusobacterium necrophorum was detected via metagenomic next-generation sequencing( mNGS). Enhanced computerized tomography showed that the left proximal jugular vein-brachiocephalic vein thrombosis. Lemierre's syndrome was diagnosed. The etiology was that the fillings in the root canal tooth lost with no blood or pain about 2 weeks before onset. The patient recovered after treatment of antibiotics and blood purification.For patients with fever, sore throat and neck pain, Lemierre's syndrome should be considered. If the loss of fillings from root canal therapy happens, especially for those with metabolic syndrome, we should be aware of the possibility of this disease. Moreover, mNGS can be used as a crucial supplementary diagnostic tool for patients with undetermined fever.